PENERAPAN METODE BERNYANYI DALAM MENGUATKAN HAFALAN MUFRADAT SANTRI MTS PMM PAKUSARI JEMBER - Hilman Triyadi F; Sofyan Rofi; Hairul Huda (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
This study aims to analyze the application of the singing method to improve the memorization of Arabic vocabulary among students at MTs Pondok Modern Muhammadiyah Pakusari Jember. The study used a Classroom Action Research (CAR) approach, implemented in two cycles: Cycle I and Cycle II. Eleven students participated in this study. Data collection involved several techniques, including observation, interviews, tests, and documentation. The results showed that the use of the singing method had a positive effect on improving the memorization of Arabic vocabulary. This was evident in the improvement in learning outcomes at each stage of the action. In the pre-cycle stage, the average score obtained by students was 13.63, with a completion percentage of 0%. Subsequently, in Cycle I, the average score increased to 40.36, although the learning completion rate remained unchanged. In cycle II, learning outcomes improved significantly, with an average score of 91.27 and a learning completion rate of 95%. In addition to improving learning outcomes, the singing method also fostered enthusiasm, increased active participation, and increased students' interest in Arabic language learning.